2014
DOI: 10.3109/14397595.2014.899178
|View full text |Cite
|
Sign up to set email alerts
|

Successful tocilizumab therapy in seven patients with refractory adult-onset Still's disease

Abstract: To evaluate the effects of tocilizumab (TCZ) on adult-onset Still's disease (AOSD), we reviewed medical records of seven patients with refractory AOSD treated with TCZ at our institution. TCZ therapy might allow rapid corticosteroid tapering and help maintain remission status, that is, resolution of clinical symptoms and normalization of biomarkers such as CRP and ferritin. Patients, however, should be monitored for the development of macrophage activation syndrome when TCZ is administered for active AOSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Since aseptic abscess is a known complication of SAPHO syndrome, TCZ treatment in our patient might have induced the aseptic abscess via exacerbating SAPHO syndrome. Indeed, in adult‐onset Still's disease (AOSD) or systemic juvenile idiopathic arthritis (sJIA), TCZ has been reported to be associated with macrophage activation syndrome (MAS), which is a serious complication of AOSD or sJIA . As previously reported, a transient increase in the serum levels of IL‐6 immediately after IL‐6 receptor blockade might induce MAS in AOSD or sJIA or induce aseptic abscess in SAPHO syndrome.…”
Section: Cytokine Serum Levels In a Patient With Sapho Syndrome At Onmentioning
confidence: 92%
See 1 more Smart Citation
“…Since aseptic abscess is a known complication of SAPHO syndrome, TCZ treatment in our patient might have induced the aseptic abscess via exacerbating SAPHO syndrome. Indeed, in adult‐onset Still's disease (AOSD) or systemic juvenile idiopathic arthritis (sJIA), TCZ has been reported to be associated with macrophage activation syndrome (MAS), which is a serious complication of AOSD or sJIA . As previously reported, a transient increase in the serum levels of IL‐6 immediately after IL‐6 receptor blockade might induce MAS in AOSD or sJIA or induce aseptic abscess in SAPHO syndrome.…”
Section: Cytokine Serum Levels In a Patient With Sapho Syndrome At Onmentioning
confidence: 92%
“…Indeed, in adult‐onset Still's disease (AOSD) or systemic juvenile idiopathic arthritis (sJIA), TCZ has been reported to be associated with macrophage activation syndrome (MAS), which is a serious complication of AOSD or sJIA . As previously reported, a transient increase in the serum levels of IL‐6 immediately after IL‐6 receptor blockade might induce MAS in AOSD or sJIA or induce aseptic abscess in SAPHO syndrome. We now recognize that our initial treatment method was wrong.…”
Section: Cytokine Serum Levels In a Patient With Sapho Syndrome At Onmentioning
confidence: 92%
“…It is characterized by elevated levels of inflammatory cytokines in serum including IL-6, IL-18, IL-1, TNFα and IFNγ. An increasing number of case reports or series has shown the effectiveness of TCZ on AOSD and reduction of glucocorticoid dose [ 117 , 118 , 119 ]. A meta-analysis of 10 studies with 147 patients showed that TCZ therapy achieved a partial remission rate in 85.38% and complete remission rate in 77.91%, and even in patients with refractory cases, the remission rate was 87.92% [ 120 ], suggesting a promising effect of TCZ on AOSD.…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…Increased levels of interleukin (IL)‐6 and other pro‐inflammatory cytokines have been shown in AOSD. Therefore, tocilizumab (TCZ), an IL‐6 receptor antagonist monoclonal antibody, has been tried in AOSD patients and successful results were reported 6‐17 . Most of the studies evaluating the treatment of TCZ are case reports involving a small number of patients, and there are several single‐centre or multi‐centre studies 6‐17 .…”
Section: Introductionmentioning
confidence: 99%